2000
DOI: 10.1161/01.cir.102.12.1351
|View full text |Cite
|
Sign up to set email alerts
|

Regular Aerobic Exercise Prevents and Restores Age-Related Declines in Endothelium-Dependent Vasodilation in Healthy Men

Abstract: Our results indicate that regular aerobic exercise can prevent the age-associated loss in endothelium-dependent vasodilation and restore levels in previously sedentary middle aged and older healthy men. This may represent an important mechanism by which regular aerobic exercise lowers the risk of cardiovascular disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
459
12
20

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 748 publications
(542 citation statements)
references
References 40 publications
43
459
12
20
Order By: Relevance
“…5. Intensive physical training may alter endothelial function (Bergholm et al 1999), whereas regular moderate physical training improves endothelial function (DeSouza et al 2000;Higashi et al 1999;Smith DT et al 2003) and attenuates the age-related peripheral vascular function changes in healthy subjects (Beere et al 1999;Martin et al 1991;Vaitkevicius et al 1993).Thus, it is uncertain whether the result of the present study can be extended to the untrained or intensively trained population.…”
Section: Discussionmentioning
confidence: 84%
“…5. Intensive physical training may alter endothelial function (Bergholm et al 1999), whereas regular moderate physical training improves endothelial function (DeSouza et al 2000;Higashi et al 1999;Smith DT et al 2003) and attenuates the age-related peripheral vascular function changes in healthy subjects (Beere et al 1999;Martin et al 1991;Vaitkevicius et al 1993).Thus, it is uncertain whether the result of the present study can be extended to the untrained or intensively trained population.…”
Section: Discussionmentioning
confidence: 84%
“…This relationship between arterial diameter and blood flow velocity (flow-diameter relationship) [29] results as the endothelial cells react to either an increase or decrease in vessel wall shear stress [8,9,10, 30]. The flow-diameter relationship [29] has been reported in the literature related to sedentary individuals [1], older populations [15, 31, 32] and individuals after SCI [4, 10, 16]. Interestingly, it has been reported that there are no significant differences in femoral artery diameter [1, 33] and blood flow velocity [1, 34] in healthy young and older adults when comparing the two limbs, which is contrary to our findings in post-stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium is an important regulator of vascular homeostasis, including control of vascular tone, smooth muscle cell proliferation, platelet aggregation, molecule adhesion, thrombosis and fibrinolysis, and solute transport into and out of the vessel (Vane et al 1990;Cannon 1998). Exercise endurance training beneficially impacts endothelial function and vasodilatory capacity (Clarkson et al 1999;DeSouza et al 2000;Hambrecht et al 2000b). It is thought that this impact is due to nitric oxide release (Kingwell et al 1997;Cannon 1998;Higashi et al 1999b) through repeated bouts of sheer stress via increased blood flow.…”
Section: Introductionmentioning
confidence: 99%